2017
DOI: 10.1016/j.jpeds.2017.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Children with Persistent and Chronic Idiopathic Thrombocytopenic Purpura: 4 Infusions of Rituximab and Three 4-Day Cycles of Dexamethasone

Abstract: Objectives To assess initial and long-term outcome of children with persistent/chronic idiopathic thrombocytopenic purpura (ITP) treated with 4 infusions of rituximab and three 4-day cycles of dexamethasone (4R+3Dex) including cohorts with most benefit and/or treatment associated toxicity. Study design All pediatric patients with ITP at Weill-Cornell who received 4R+3Dex were included in this retrospective study. Duration was median time from first rituximab infusion to treatment failure. Patient cohort incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 32 publications
5
27
0
Order By: Relevance
“…One study combined rituximab with dexamethasone and demonstrated an initial response rate of 45% and a relapse rate of 40% after 60 months (evidence level III). 276 In adolescent female patients with ITP duration , 24 months, 47% maintained long-term remission without further therapy. 276 The studies of rituximab in children with ITP report that the treatment is generally well tolerated, with low levels of urticarial rash, headache, chills, fever, and abnormal Ig levels.…”
Section: Emergency Treatment In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…One study combined rituximab with dexamethasone and demonstrated an initial response rate of 45% and a relapse rate of 40% after 60 months (evidence level III). 276 In adolescent female patients with ITP duration , 24 months, 47% maintained long-term remission without further therapy. 276 The studies of rituximab in children with ITP report that the treatment is generally well tolerated, with low levels of urticarial rash, headache, chills, fever, and abnormal Ig levels.…”
Section: Emergency Treatment In Childrenmentioning
confidence: 99%
“…276 In adolescent female patients with ITP duration , 24 months, 47% maintained long-term remission without further therapy. 276 The studies of rituximab in children with ITP report that the treatment is generally well tolerated, with low levels of urticarial rash, headache, chills, fever, and abnormal Ig levels. No cases of longterm toxicity due to B-cell depletion have been reported.…”
Section: Emergency Treatment In Childrenmentioning
confidence: 99%
“…21 A small percentage of patients developed chronic TIP, despite the natural history of the disease, which states that 13 to 36% will develop a chronic, refractory, and difficult to control form. 22 This is a low frequency, compared with similar international and national studies. [12][13][14]16,19 Only one of these patients had an insidious onset (risk factor for chronicity) and that same patient was the only one with a history of infection (protective factor); 75% of them received therapies recommended by the MCPG.…”
Section: Discussionmentioning
confidence: 72%
“…While autoreactive B cells may return in some patients following RTX, 18 the impact on disease outcome is not closely linked to circulating antibody levels, and the diverse function of B cells including their impact on T cell activity may explain why there may be an effect of RTX many years postadministration. [19][20][21][22] B lymphocyte depleting immunotherapy appears to have disease-modifying activity in adults with Graves' hyperthyroidism; RTX administration has been associated with encouraging remission rates, with approximately 50% of thyrotoxic adults in case reports and case series becoming euthyroid following treatment with RTX. [23][24][25][26][27][28] Many of these patients were selected on the basis of more severe disease with relapsed Graves' hyperthyroidism or aggressive orbitopathy.…”
Section: Introductionmentioning
confidence: 99%